IMPLEMENTATION OF THE INDEPENDENT CURRICULUM AT SMA NEGERI 1 SOSORGADONG BASED ON 4C COMPETENCIES (Critical Thiking, Creative Thinking, Collaboration and Communication) - Rafi'i, Mhd. Rafi'i Ma'arif Tarigan; Dwi Rahmadani Purba; Indah Sarina Sihaloho; Rostaida Sitompu; Yuri Indri Yani; Muhammad Iqbal; Ruminda Hutagalung; Tanjung, Hotman Efendi (Cemara Education and Science, 2023)
ABSTRACT The purpose of this study is to describe 4C competency in implementing Merdeka Curriculum in class III of SMA Negeri 1 Sosorgadong. This research uses descriptive qualitative type research involving class III students at SMA Negeri 1 Sosorgadong, totaling 28. The data collection techniques used are observation and documentation. The 21st century skills that students must have are Critical Thinking (critical thinking), Creativity (creativity), Communication (communication), and Collaboration (working together) which are often abbreviated as 4C. The 4C competencies in the implementation of the independent curriculum can be practiced in learning, especially class III SMA. It is recommended that educators use 4C competencies in every learning activity in order to produce competent, quality students who have skills that can be used in everyday life.